Correlation of Volume and Intracerebral Site with Hemorrhagic Stroke Mortality Based on CT Scan - Andi Rizal; Arif Faisal; Sri Retna Dwidanarti (Academic Hospital Journal, 2018)
Background: Intracerebral hemorrhage is a bleeding in the brain’s parenchyma that can extend into the ventricles, and in rare cases into the subarachnoid area. The effects of hemorrhage volume are from mild to severe clinical symptoms due to the increased intracranial pressure. Head CT scan is used to rule out other causes than stroke.Objective: This study aimed to determine the correlation of intracerebral hemorrhage volume and hemorrhage site with mortality of hemorrhagic stroke patients based on head CT scan tests.Design: This research used analytic observational methods to conduct a positive correlation assessment of volume and hemorrhage site with mortality in intracerebral hemorrhagic stroke patients. The study used a cross-sectional design with retrospective data. Data were assessed from 55 cases consisting of 29 men and 26 women.Results: The commonest hemorrhage was found in 24 cases (43.6%) in ganglia basalis, 15 cases (27.3%) in lobus parietalis and 8 cases (14.5%) in pons. Blood volume decreased to 25 cc in 35 cases (63.6%), 25-50 cc in 13 cases (23.6%), and decreased to more than 50 cc in 7 cases (12.7%). Correlations of contingency coefficient tests between mortality and hemorrhage site in lobar were (r=0.049, p=0.714), in deep artery territories (r=0.170, p=0.200) and in brain stem (r=0.298, p=0.020). Meanwhile, correlations between mortality and decreased blood volume to 25 cc were (r=0.589, p=0.000), in 25-50 cc (r=0.406, p=0.001) and for blood volume more than 50 cc (r=0.437, p=0.000).Conclusions: There was positive correlation between mortality and hemorrhage site in brain stem while in lobar and in deep artery territories there was no correlation with mortality and hemorrhage site. There were positive correlations between intracerebral hemorrhage volume and mortality with moderate correlation strength.